BIMBINGAN DAN KONSELING DI ERA DISRUPSI - Eka Dewi Sri Wahyuni (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2022)
The era of disruption in education has an impact on the level of competition that is getting tougher so that various efforts are needed to form and prepare the younger generation so that they can become excellent human resources, tough and able to face the challenges of the times. Therefore, the need for a professional guidance and counseling teacher is an important point. This happens because the BK teacher has a duty to guide students. Guidance is the process of providing assistance carried out by an expert to one or several people, both children, adolescents and adults. The goal is that the person being mentored can develop their own abilities and be independent by utilizing individual strengths and existing facilities and can be developed based on applicable norms. Guidance and Counseling (BK) is expected to be present to help answer problems that arise as a result of changes in the era of disruption. Various kinds of innovation, creativity and modification of digital technology can have an impact on various mastery and utilization of science and technology.